Prevalence of Zoonotic Gastrointestinal Helminth Parasite among Dogs in Suryabinayak, Nepal - Punya Ram Sukupayo; Semsal Tamang (Veterinary Medicine International)
Dogs are popular pets around the world and have always had a very close relationship with humans. Zoonotic gastrointestinal helminth parasites are a great threat to both stray and pet dogs. This study was carried out to determine the prevalence of zoonotic gastrointestinal helminths in dogs. 400 samples were collected, including 200 from pet dogs and 200 from stray dogs. The samples from pet dogs were collected from the ground immediately after voiding with the help of the owner, whereas stray dogs were caught by using a dog catcher, and the samples were collected directly from the rectum by using a gloved index finger. All collected samples were examined under a microscope using sedimentation and flotation techniques. The overall prevalence of infection was found to be 59.50%, with a significantly higher prevalence in stray dogs (70%) than that in pet dogs (49%). Ancylostoma spp., Toxocara spp., Trichuris spp., Capillaria spp., Dipylidium caninum, and Taenia/Echinococcus spp. were six different species found in the current study. The study showed the highest prevalence of Ancylostoma spp. (49.16%) and the least prevalence of Capillaria spp. (0.84%). In the age-wise study, puppies had a significantly high infection rate (86.96%). Similarly, we recorded a significantly higher prevalence of intestinal helminths among nondewormed pet dogs (78.65%) than among dewormed pet dogs (25.23%). This study highlights the severe environmental contamination shed by dogs, causing a higher risk of zoonotic transmission. It indicates the urgent need to manage these parasites in dogs and educate the public on how to care for their pets and the parasites they shed.